Report of the first workshop on the genetic map of bovine chromosome 1 - Taylor, J.F.; Brenneman, R.A.; Burns, B.M.; Davis, S.K.; Yeh, C.C.; Bishop, M.D.; Eggen, A.; Vaiman, D.; Aleyasin, A.; Armitage, S.M.; Barendse, W.; Beever, J.E.; et al. (Wiley, 1998)
A report of the first workshop on the genetic map of bovine chromosome 1 (BTA1) is presented. Five laboratories contributed 31 962 informative meioses from 70 loci. Thirty-two loci which had been typed by at least two laboratories were used to construct a framework genetic map with a likelihood ratio support of at least 1000:1 for locus order. The resulting sex-averaged framework map contained 26 loci and spanned 163.6 CM. The lengths of the female and male maps were 159.5 CM and 165.3 CM, respectively, and there was evidence for an expansion in the telomeric one-third of the male map. Of the four cases where order for closely linked loci differed among the maps produced for each of the contributing laboratories, a consensus order was obtained for three in the framework map. The average genetic distance between framework loci on the sex-averaged map was 6.3 CM.